Planeamiento estratégico para mejorar el desempeño financiero y creación de valor de la empresa Neo Motors Lima SAC - Año 2016 - Zavaleta León, Roger Eduardo (2018)
The present investigation has as purpose to implement a Strategic Planning to be able to improve the financial performance and creation of value of the company Neo Motors Lima for the period 2016. In order to develop this research, a study was made of the economic, financial and organizational information that the company has, as well as internal and external risks, to later elaborate an action plan to be able to improve the profitability and creation of value for subsequent years. To this end, an Inductive, Analytical, Statistical and Dialectic type study has been designed, the information of the financial statements was analyzed by performing various modalities and applying Direct Observation. The results found are shown in tables and statistical figures in a detailed and orderly manner, where it was determined that the company has not previously carried out a Strategic Planning. Therefore, the research is being directed, through a financial analysis and making a diagnosis of the policies, so that it can improve financially and be profitable; also that the planning will contribute to a better strategic management with respect to its results of liquidity, solvency, indebtedness and profitability. The research concludes the importance of strategic planning for good financial, economic, organizational and value creation in a company, and meet the objectives and goals of a medium and long term.